2002
DOI: 10.1002/ajmg.10510
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal sterol metabolism in a patient with Antley‐Bixler syndrome and ambiguous genitalia

Abstract: Antley-Bixler syndrome (ABS) is a rare multiple anomaly syndrome comprising radiohumeral synostosis, bowed femora, fractures of the long bones, premature fusion of the calvarial sutures, severe midface hypoplasia, proptosis, choanal atresia, and, in some, ambiguous genitalia. Of fewer than 40 patients described to date, most have been sporadic, although reports of parental consanguinity and affected sibs of both sexes suggests autosomal recessive inheritance in some families. Known genetic causes among sporadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
78
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 36 publications
2
78
0
Order By: Relevance
“…Cholesterol biosynthetic P450 enzymes were implicated by reports that infants of mothers treated with fluconazole (an antifungal agent that interferes with yeast ergosterol synthesis by inhibiting lanosterol 14α-demethylase) had a pattern of congenital malformations that resembled ABS 3,4 . Mutations in human genes CYP17A1 (encoding P450c17; located at 10q24.3), CYP21A2 (encoding P450c21; located at 6p21.3) and CYP51A1 (encoding lanosterol 14α-demethylase; located at 7q21.2-q21.3) have been sought but not found 2,4,5 . We suggested that defects in P450c17 and P450c21 might be due to mutant POR, the flavoprotein that donates electrons to all microsomal P450 enzymes 6 , but the affected individuals lacked apparent disorders of bile acid synthesis or drug metabolism, which also require P450 enzymes, and knock-out of POR is embryonically lethal in mice 7,8 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cholesterol biosynthetic P450 enzymes were implicated by reports that infants of mothers treated with fluconazole (an antifungal agent that interferes with yeast ergosterol synthesis by inhibiting lanosterol 14α-demethylase) had a pattern of congenital malformations that resembled ABS 3,4 . Mutations in human genes CYP17A1 (encoding P450c17; located at 10q24.3), CYP21A2 (encoding P450c21; located at 6p21.3) and CYP51A1 (encoding lanosterol 14α-demethylase; located at 7q21.2-q21.3) have been sought but not found 2,4,5 . We suggested that defects in P450c17 and P450c21 might be due to mutant POR, the flavoprotein that donates electrons to all microsomal P450 enzymes 6 , but the affected individuals lacked apparent disorders of bile acid synthesis or drug metabolism, which also require P450 enzymes, and knock-out of POR is embryonically lethal in mice 7,8 .…”
mentioning
confidence: 99%
“…Sequencing of POR showed that individual 2 was heterozygous with respect to the missense mutation 1475T→A (leading to the amino acid substitution V492E; also found on the maternal allele) but detected no mutations in the exons or first 50 bp of splice donoracceptor sites on the paternal allele. Individual 3 had genital ambiguity, typical findings of ABS and abnormal sterol metabolism, but no steroidal data are available 5 ; he was apparently homozygous with respect to the substitution 859G→C (leading to the amino acid substitution A287P), and his mother was heterozygous (paternal DNA was not available To assess the activities of the POR mutants, we expressed each in Escherichia coli and measured the ability of bacterial membranebound proteins to receive electrons from NADPH and donate them to cytochrome c (see Supplementary Methods online). All five of the missense mutations markedly reduced both the capacity to oxidize NADPH and the catalytic efficiency (V max /K m ) of the reduction of cytochrome c ( Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pathogenesis of skeletal malformations in POR deficiency is unclear, it has been suggested that cholesterol biosynthesis and POR may be involved in skeletal development. Examples include Smith-Lemli-Opitz syndrome, which shows complex skeletal malformations caused by mutations in the gene encoding 7-dehydrocholesterol reductase [15], and fluconazole-induced ABS, which is caused by inhibition of POR-dependent 14α-demethylase [11].…”
Section: Discussionmentioning
confidence: 99%
“…ABS is characterized by craniosynostosis, radio/ humeral synostosis, ambiguous genitalia, and other congenital anomalies. In addition, some patients with ABS showed abnormal steroid hormone profiles of elevated serum 17-hydroxyprogesterone and low cortisol levels (25)(26)(27). These endocrine findings have strongly suggested that there is a genetic defect of steroid biosynthesis in ABS.…”
Section: Por Deficiecnymentioning
confidence: 99%